Etiquette & espionage ebook - Carriger, Gail (Finishing School, 2013)
This steampunk series debut set in the same world as the New York Times bestselling Parasol Protectorate is filled with all the saucy adventure and droll humor Gail Carriger's legions of fans have come to adore. Fourteen-year-old Sophronia is a great trial to her poor mother. Sophronia is more interested in dismantling clocks and climbing trees than in proper manners—and the family can only hope that company never sees her atrocious curtsy. Mrs. Temminnick is desperate for her daughter to become a proper lady. So she enrolls Sophronia in Mademoiselle Geraldine's Finishing Academy for Young Ladies of Quality. But Sophronia soon realizes the school is not quite what her mother might have hoped. At Mademoiselle Geraldine's, young ladies learn to finish...everything. Certainly, they learn the fine arts of dance, dress, and etiquette, but they also learn to deal out death, diversion, and espionage—in the politest possible ways, of course. Sophronia and her friends are in for a rousing first year's education.